2020
DOI: 10.1002/alz.12229
|View full text |Cite
|
Sign up to set email alerts
|

Nerve growth factor (NGF) pathway biomarkers in Down syndrome prior to and after the onset of clinical Alzheimer's disease: A paired CSF and plasma study

Abstract: Background The discovery that nerve growth factor (NGF) metabolism is altered in Down syndrome (DS) and Alzheimer's disease (AD) brains offered a framework for the identification of novel biomarkers signalling NGF deregulation in AD pathology. Methods We examined levels of NGF pathway proteins (proNGF, neuroserpin, tissue plasminogen activator [tPA], and metalloproteases [MMP]) in matched cerebrospinal fluid (CSF)/plasma samples from AD‐symptomatic (DSAD) and AD‐asymptomatic (aDS) individuals with DS, as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 90 publications
2
19
0
Order By: Relevance
“…In a later study that quantified the levels of several NGF pathway proteins (proNGF, neuroserpin, tissue plasminogen activator (tPA), and metalloproteases) in samples from AD-asymptomatic DS (n = 14), prodromal AD (n = 10) DS, AD dementia (n = 12), and controls (n = 16), ProNGF and MMP-3 levels were elevated, while tPA was decreased in plasma in individuals with DS. The plasma levels of neuroserpin and MMP-9 were similar between all groups [116].…”
Section: Cholinergic and Adrenergic Biomarkersmentioning
confidence: 77%
“…In a later study that quantified the levels of several NGF pathway proteins (proNGF, neuroserpin, tissue plasminogen activator (tPA), and metalloproteases) in samples from AD-asymptomatic DS (n = 14), prodromal AD (n = 10) DS, AD dementia (n = 12), and controls (n = 16), ProNGF and MMP-3 levels were elevated, while tPA was decreased in plasma in individuals with DS. The plasma levels of neuroserpin and MMP-9 were similar between all groups [116].…”
Section: Cholinergic and Adrenergic Biomarkersmentioning
confidence: 77%
“…Analysis of NGF pathway proteins in matched CSF/plasma samples from DSAD and individuals with DS aDS, as well as controls, revealed that the levels of the 50 kDa isoform of proNGF and MMP9 in CSF were competent to identify symptomatic AD from the wider DS population. Both members of the NGF metabolic pathway identified symptomatic AD from the wider DS population with a sensitivity and specificity matching or outperforming that of the classical AD CSF biomarkers pTau, tTau, and the AB42/40 ratio ( Pentz et al, 2021a ). Importantly, longitudinal increases in 50 kDa proNGF levels in plasma over 1 year correlated to prospective cognitive decline over the subsequent 2 years ( Iulita and Cuello, 2016 ), demonstrating a potential value of NGF-related biomarkers in identifying incipient cognitive decline in this population.…”
Section: Ngf Metabolic Pathway Related Biomarkers As Indicators Of Ad Pathology In Dsmentioning
confidence: 95%
“…Several studies have demonstrated that changes in plasma Aβ40 and Aβ42 in DS correlate with AD onset ( Schupf et al, 2007 ; Jones et al, 2009 ; Matsuoka et al, 2009 ; Schupf et al, 2010 ; Coppus et al, 2012 ). As for Tau, increases in CSF total Tau (tTau) and phosphorylated Tau (pTau), have been correlated with AD onset in DS ( McGlinchey et al, 2020 ; Pentz et al, 2021a ). Likewise, plasma neurofilament light (NfL), and IL1β, have been shown in multiple studies to reliably distinguish DSAD individuals with DS asymptomatic for AD (aDS) ( Petersen and O’Bryant, 2019 ; Startin et al, 2019 ; McGlinchey et al, 2020 ).…”
Section: Ngf Metabolic Pathway Related Biomarkers As Indicators Of Ad Pathology In Dsmentioning
confidence: 99%
See 1 more Smart Citation
“…Progress in the cell cycle depends on the coordination and interaction of trophic factors with two categories of regulatory proteins, including cyclins and cyclin-dependent kinases (CDKs) [11,12]. For instance, nerve growth factor (NGF) inhibits the induction of cyclins and their associations with specific CDKs, hence interrupting cell cycle reentry through the G1-phase [13]. Insulin-like growth factor 1 (IGF-1) prevents the expression of cell cycle proteins (e.g., cyclin A, D1, and CDK2) known to stimulate G1 quiescent cells to enter the S-phase [14].…”
Section: Introductionmentioning
confidence: 99%